Existence of Marginal Cost Pricing Equilibria in Economies with Several Nonconvex Firms - Bonnisseau, Jean-Marc; Cornet, Bernard (Econometrica, 1990)
This paper considers a general equilibrium model of an economy where some firms may exhibit increasing returns to scale or more general types of nonconvexities. The firms are instructed to follow the standard marginal cost pricing rule or to fulfill the first-order necessary conditions for profit maximization. A general existence theorem of equilibria is proved in the case of an arbitrary number of firms. No assumption is made to imply the aggregate productive efficiency of equilibria, a condition that must be excluded in the nonconvex case. Copyright 1990 by The Econometric Society.